PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE VASOS DE VIDRIO A BASE DE MATERIAL RECICLADO EN LA CIUDAD DE LOJA - MACAS CABRERA, KEVIN SANTIAGO (2020)
The present feasibility project is with the objectivity of publicizing the results obtained, from the study carried out of the implementation of a company that produces and markets glass cups made from a base of recycled material in the city of Loja, in order to take the decision to invest or not in the implementation of the company, the use of its methods and techniques for the present investigation, direct observation techniques and the survey that was applied to families in the city of Loja; In addition to these techniques, inductive and deductive methods were used in order to have both general and specific logical reasoning. In addition to applying the data collection technique for the analysis of supply and demand, Obtaining as results that in the location market there is on average an unsatisfied demand of 922,450, that the tastes and recommendations regarding glass cups of the plaintiffs , are the medium-sized and colorless glasses, that is, transparent, the most suitable means of communication for the company's advertising and the offer of this product, are social networks. Through research, it was possible to determine that there is a large amount of raw material for the production of the product, and in the city, it is easily found what is necessary to produce, such as electrical machines, tools and other items that are required for daily work. The main conclusions are that if the company is implemented, the product has an effective demand of 95% acceptance, that the investment of the project is $ 48,383.87 for a duration of 10 years of useful life of the company, generating positive results. in the profit and loss statement, on average from year 1 with $ 9,592.75 to year 10 with $ 12,829.93, having the money invested to be recovered in year 5, with 5 months, and 19 days of work , giving us a benefit-cost ratio of 4 0.43 ctvs for every dollar invested. Finally, it is concluded that the project is totally feasible from a technical, legal, and financial point of view, recommending it for its implementation.